Challenging Design-Based Research : editorial - Emmler, Tina [Verfasser]; Euler, Dieter [Verfasser]; Ertl, Hubert [Verfasser] (My University, 2020)
This editorial gives a short overview of how the term "Design-based Research" (DBR) has emerged over the past 20 years and how it is now located in the research landscape. In the second section the title "Challenging Design-Based Research" that was choosen for this special issue of EDeR is described. On the one hand the title implies that the researcher is challenged by DBR. On the other hand it also means that the research community depends on the involvement of each and every member. As a consequence, it is not only the single researcher who is challenged by DBR - it is DBR itself that is and needs to be challenged by the researcher and the community. Finally, the contributions of the special issue are summarized. (BIBB-Doku)
Keywords: T 1 Forschungsrichtungen; T 3 Forschungsmethoden; Berufsbildungsforschung; Gestaltungsbasierte Forschung; Aktionsforschung; Forschungsmethode; Forschungsumsetzung; Forschungskooperation; Theorie-Praxis